SELECTION TEST OF NEW VARIETIES (International Bulletin of Medical Sciences and Clinical Research, 2023)
Andijan-35 (2006), Andijan-36 (2009), Andijan-37 (2012), Ibrat (2011), UzPITI-202 (2021) cotton varieties created at the Andijan scientific experimental station were regionalized and included in the State Register, New UzPITI-201 (2013), UzPITI-203 (2017), SP-204 (2021) were considered to be promising, the varieties SP-206, SP-207, SP-209 created after them are being tested in the State variety testing networks, and the varieties and lines are valuable for the economy Information about the signs is provided.